Korean Crisis and Recovery - Coe, David (International Monetary Fund, 2002)
Edited by David T. Coe and Se-Jik Kim, this volume contains papers presented at a May 2001 conference in Seoul sponsored by the IMF and the Korea Institute for International Economic Policy on the Korean Crisis and Recovery. The papers examine the response to the 1997 crisis, its long-term impact on growth, and the state of financial and corporate sector reforms. Authors include academics, Korean policymakers, and IMF and World Bank staff involved in the Korean program.